سنت :معنی ومفہوم اور اشکالات کا حل: Sunnah: Interpretation and Resolution of Doubts (Al-Qamar, 2023)
The sub-continent was under the rule of the British for three centuries during 17th to 20th century. They were Christians by their religion; they built a policy to capitalize on the decadence of Muslims. They were trying to deviate the religion from the real values. The British planted different communities as Arya, Hindu, Natury and Qadianis so no Muslim should resort to Islam, flare up upon the desecration of Holy Quran and Sunnah demand death sentence for any person who spoke disrespectfully of sacred things and who differentiate between what is forbidden in Islam A major attack in these attacks was that they tried to destroy the importance of the Sunnah of the Prophet (S.W) among Muslims, in which they succeeded to some extent. are active to extract from the hearts of. Therefore, in this paper, an attempt has been made to highlight the importance of Sunnah and remove the problems related to it.
Keywords: Sub-continent; Sunnah; Muslims; importance; Qadianis